ANALISA PERKEMBANGAN PENERIMAAN PAJAK BBNKB SEBAGAI PENDAPATAN ASLI DAERAH PADA DIPENDA SAMSAT CIBINONG - sabil, sabil (Universitas Bina Sarana Informatika, 2016)
Reception is one country and use the revenue to finance public expenditures associated with the task of organizing state government. This study aims to determine the level of tax revenue transfer tax motor vehicles which are in DIPENDA SAMSAT Cibinong. Data collection methods are observation, interviews and documentation analysis methods such as qualitative methods. Tax transfer tax motor vehicles each year has increased, this was due to the desire some people were so great to own a private vehicle as a means of land transportation in order to achieve a certain goal. The data obtained show that the income tax transfer tax motor vehicles in 2011, 2012, 2013 respectively acceptance over the target with the realization of 236.74%, 306.3%, 357.86%, on average over the period three years, the number of realization is 336.23%, which indicate where the period of 2011 to 2013 tax revenues of Customs of Vehicle always exceeded the planned target. This is influenced by people's desire to have a motor vehicle in either two-wheel or four wheel as the vehicle for daily activities and this is one of the original income. Keywords : Tax Revenue, BBNKB, Locally-generated revenue